Clinical Factors Associated With Practice Variation in Discharge Opioid Prescriptions After Pancreatectomy. Issue 1 (July 2020) - Newhook, Timothy E.; Vreeland, Timothy J.; Dewhurst, Whitney L.; Wang, Xuemei; Prakash, Laura; Feng, Chun; Bruno, Morgan L.; Kim, Michael P.; Aloia, Thomas A.; Vauthey, Jean-Nicolas; Lee, Jeffrey E.; Katz, Matthew H. G.; et al.
Abstract : Objective: To characterize opioid discharge prescriptions for pancreatectomy patients. Background: Wide variation in and over-prescription of opioids after surgery contribute to the United States opioid epidemic through persistent use past the postoperative period. Objective strategies guiding discharge opioid prescriptions for oncologic surgery are lacking, and factors driving prescription amount are not fully delineated. Methods: Characteristics of pancreatectomy patients (March 2016–August 2017) were retrospectively abstracted from a prospective database. Discharge opioids prescriptions were converted to oral morphine equivalents (OME). Regression models identified variables associated with discharge OME. Results: In 158 consecutive patients, median discharge OME was 250 mg (range 0–3950). Discharge OME was labeled "low" (<200 mg) for 33 patients (21%) and "high" (>400 mg) for 38 (24%). Only shorter operative time (odds ratio [OR]—0.14, P = 0.004) and inpatient team (OR—15.39, P < 0.001) were independently associated with low discharge OME. Older age was the only variable associated with high discharge OME. Fifty-seven patients (36%) used zero opioids in the last 24-hours predischarge, yet 52 of 57 (91%) still received discharge opioids. Older age (OR—1.07), grade B/C pancreatic fistula (OR—3.84), and epidural use (OR—3.12) were independently associated with zero last-24-hours OME (all P ⩽ 0.040). Conclusions: The wide variation in discharge opioid prescriptions is heavily influenced by provider routine/bias and not by objective criteria such as last-24-hours OME. Quality improvement strategies could include aggressive weaning protocols to increase the proportion of patients with zero/near-zero last-24-hour OME and limiting prescriptions to a conservative multiplier of the last-24-hour OME.